Prediction of Bottom-Hole Flowing Pressure using general regression neural network - Memon, P.Q. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper presents the application of Surrogate Reservoir Model (SRM) for predicting the Bottom-Hole Flowing Pressure (BHFP) on an initially undersaturated reservoir. SRM is recently introduce technology that is used to replicates the results of numerical simulation model. High computational cost and long processing time limits our ability to perform comprehensive sensitivity analysis and quantify uncertainties associated with reservoir because reservoir model that contains large number of grids in its geological structure takes considerable amount of time for a single simulation run. And also making hundred and thousands simulation runs is considered as a cumbersome process and sometimes impractical. SRM is considered as as a solution tool to tackle this issue. SRM uses Artificial Neural Network (ANN) technique for the reservoir simulation and modeling. In this paper, the results of SRM for predicting BHFP is presented and a reservoir simulation model has been presented using Black Oil Applied Simulation Tool (BOAST). To build any SRM, it requires small number of runs to train the model. Once we train the SRM, it can generate hundred and thousands of simulation runs in a matter of seconds. As a part of this system, it is proposed to develop a SRM extraction based on ANN to enhance the realization run time. Â© 2014 IEEE.